Optimizing Agricultural Labour: An Examination of On-Demand Workforce Solutions for Seasonal Demands (International Journal of Scientific Research in Science and Technology, 2025)
To address the growing challenges in managing on-demand Labour within the agricultural sector, we introduce Agro Finder, an innovative application developed using Figma for design and flutter for frontend development and firebase for backend. This research presents a comprehensive overview of the current state of Labour management in agriculture and proposes Agro Finder as a solution tailored to the sector's unique needs. The app leverages real-time data and sophisticated algorithms to streamline the connection between farmers and Labourers, optimizing Labour allocation based on geographic location, skills, and availability. Further analysis reveals that Agro Finder significantly enhances Labour utilization efficiency, reducing downtime in agricultural operations. The app's intuitive design, supported by Figma, ensures a user-friendly experience, while the fronted, powered by Flutter, provides reliable performance. The integration of these technologies facilitates efficient Labour management, leading to increased productivity and operational efficiency in agriculture. The research findings underscore the potential of applying modern development tools and methodologies to solve traditional problems in agriculture. By harnessing the power of Figma and Flutter, Agro Finder sets a new standard in on- demand Labour management, offering valuable insights and practical solutions. This study provides a solid foundation for future advancements in agricultural Labour management and highlights the importance of technological innovation in enhancing agricultural productivity.
Keywords: on-demand Labour; agricultural management; mobile application development; Figma; Flutter; Labour allocation; data processing; Firebase